APLIKASI EMAIL CLIENT MULTI-PLATFORM DENGAN ENKRIPSI DATA BERBASIS JAVA - Ridwan; Adhi Susano (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Client is an application that is used to send and receive e-mails through your computer without a browser. Simply by running the e-mail client application, the e-mail will automatically be downloaded to your computer. The more varied operating systems used by Users also sometimes make Users have to change email clients when moving operating systems, for example Windows Users who are used to Outlook have to use evolution on Linux, whereas when using Mac OS they have to use the Mail program. This is of course inconvenient for the User. Not to mention the security of the clinet email itself. In this research, software has been created to reduce existing problems. The method used in the design and manufacture of this software is the Guidelines for Rapid Application Engineering (Grapple) method. This software was created using Netbeans 7.0. This multi-platform email client application program with base64 encoding on a desktop base can run on three operating systems, namely Windows, Linux and Macinthos. This application can also encode with the base64 algorithm the contents of the message so as to maintain the confidentiality of the contents of the message in the email client itself.